The migrant penalty in Latin America: Experimental evidence from job recruiters - Wladimir Zanoni; Raissa Fabregas (Inter-American Development Bank (IDB), 2024)
We conducted an artifactual field experiment with human resource recruiters in Ecuador to investigate the extent to which migrants are penalized in the labor market. Human resource recruiters were hired to evaluate pairs of job candidates competing for jobs. The candidate profiles were observationally equivalent, except that one was randomly assigned to be a Venezuelan migrant. Recruiters assessed job fitness, proposed wages for each candidate, and made hiring recommendations. We find robust evidence of a penalty against migrants across all dimensions. Venezuelans are penalized despite being from a population who shares cultural, historical, and linguistic characteristics with natives and has, on average, higher levels of education. We do not find evidence that recruiters demographic characteristics, experience, cognitive scores, or personality traits correlate with a preference for natives. Instead, there is suggestive evidence that jobs requiring a greater degree of local knowledge or public interface carry a higher migrant penalty.
Keywords: J71; J61; C93; O15; 330; Migrant; Labor Market; Wage